SOSIALISASI PENGELOLAAN SAMPAH: MEMBANGUN DESA CIBODAS MENUJU ZERO WASTE MELALUI INOVASI ROCKET STOVE OLEH KKM KELOMPOK 71 UNIVERSITAS SULTAN AGENG TIRTAYASA - Jumbuh Prabowo; Ahmad Akmal; Rafi Ramadhan Asshidieqie; Diana Debora Ginting; Ester Imma A R Panggabean; Dinda Friska Maulia; Dewi Oktavia Putri; Gagah Hanugrah; Mochammad Randy Pratama; Aulia Nufus Suzakiah; Siti Nazwa Nurul Aziza; Nova Tiara Chanra; Tegar Gusti Anggara; Oky Rhamdani; Narita Maulidya Putri; Rizqi Ghinansyah; Ratu Lusiana Damayanti; Elsa Aprilia Dini; Najwa Riska Humairah; Rulinda Reva Dena Nabila; Naeli Tamamah (SEBA: Jurnal Pengabdian kepada Masyarakat, 2026)
Household waste problems continue to increase and require community-based integrated management. This community service activity aimed to improve public awareness and knowledge regarding zero waste-based waste management and to introduce a simple technological innovation in the form of a rocket stove. The activity was conducted on January 24, 2026, in Cibodas Village, Tanara District, Serang Regency, involving 38 community members and 20 university students. The methods used included counseling, interactive discussions, and demonstrations. The results showed an increase in community understanding of waste sorting and utilization, as well as strong interest in the rocket stove as an alternative solution for reducing dry waste and producing useful residues. This program is expected to support the realization of a clean, healthy, and sustainable village. Keywords: community participation; waste management; rocket stove; zero waste